2016
DOI: 10.5897/ajar2016.11304
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and silicon fertilizer rates effects on dynamics of soil phosphorus fractions in oxisol under common bean cultivation

Abstract: The purpose of this research was to evaluate the effects of P and Si fertilizer rates in dynamic of P fractions in clay soil under greenhouse. The research was carried out in a Dystroferric Red Latosol of a very loamy texture from Lavras city, Minas Gerais State, Brazil. The experimental design was entirely randomized, arranged in 4 × 3 factorial design, with four repetitions. The treatments included four inorganic fertilizer P rates (0, 110, 330 and 560 mg dm ). The preview application of Si fertilizer did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The Pi-NaOH 0.5 fraction was the majority buffering of the labile fractions, and lower clay content explain the generalized reduction of Pi-NaOH 0.5 fraction, which is the most labile fraction observed. As observed by Santos et al (2008) and Alovisi et al (2016), the lower labile fraction participated in P supply for plants, proved by its decreasing in total P through time of P-fertilizer.…”
Section: Soil Inorganic Phosphorus (Pi) Fractionsmentioning
confidence: 75%
See 2 more Smart Citations
“…The Pi-NaOH 0.5 fraction was the majority buffering of the labile fractions, and lower clay content explain the generalized reduction of Pi-NaOH 0.5 fraction, which is the most labile fraction observed. As observed by Santos et al (2008) and Alovisi et al (2016), the lower labile fraction participated in P supply for plants, proved by its decreasing in total P through time of P-fertilizer.…”
Section: Soil Inorganic Phosphorus (Pi) Fractionsmentioning
confidence: 75%
“…P distribution in soil is present in net crystalline of some soil mineral until more stable fractions as organic matter, which compose the total P fractions in soil that is constituted of organic and inorganic fractions. These organic and inorganic P fractions in soil are present under dynamic balance (Alovisi et al, 2016). P adsorption is directly correlated with clay content in soil due to capacity of P adsorption in broken face of silicate clay as well as iron (Fe) and aluminum (Al) oxi-hydroxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achat et al 1 the results show the dominant role of aluminum and iron oxides and organic carbon in the control of the dynamics of phosphate ions in acidic and non-acidic soils. Alovisi et al 2 showed that the effect of inorganic fertilizer on the moderate and labile P fractions was high. The NaHCO 3 -Po fraction in the organic P fractions was observed to be the only fraction that contributed to the plant nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have been using the fraction proposed by Hedley [44,[54][55][56]]. Hedley's fractionation is widely used [57], majority in researches about P dynamic and cycling in soil associated with primary material, soil tillage, and use into diverse crop systems.…”
Section: Determination Of P Formsmentioning
confidence: 99%